Labour Market Reforms in Japan to Improve Growth and Equity - Jones, Randall S.. (OECD Publishing, 2011)
Traditional Japanese labour market practices, which benefited both workers and firms during the highgrowth era, are no longer appropriate in the context of slow economic growth and rapid population ageing. Reforms are needed in light of the upward trend in non-regular employment to break down labour market dualism and to encourage greater labour force participation by women, the elderly and youth. A comprehensive approach that includes improving the social insurance coverage of non-regular workers and upgrading training programmes for them, preventing discrimination against non-regular workers and reducing effective employment protection for regular workers would increase labour market flexibility and human capital. Moreover, such reforms would increase equity across different segments of the labour force. Drawing more women into the labour force requires removing financial disincentives to work, creating more family-friendly workplaces and increasing the availability of childcare. The labour force participation of the elderly should be raised by promoting continuous employment and abolishing mandatory retirement. More effective vocational training is needed for younger workers. This Working Paper relates to the 2011 OECD Economic Survey of Japan (www.oecd.org/eco/surveys/Japan)
Keywords: Economics; Japan